IMPLEMENTASI VPN DIATAS ROUTING OSPF DALAM MEMBANGUN SIMULASI JARINGAN MAN - Nezza Anggraini Yolandari; Delvita Aulia Artika; Bunga Dwi Febrianti; Dedy Kiswanto (LPPM Universitas Dhyana Pura, 2025)
This study aims to compare the effectiveness of the Virtual Private Network (VPN) Ipsec and GRE tunnel protocols in establishing site-to-site VPN connections on a Metropolitan Area Network (MAN) optimized with Open Shortest Path First (OSPF) routing. Using Cisco packet tracer software, simulations were conducted involving seven routers as representations of different locations, connected via VPN connections. The simulation results show that although Ipsec offers significant security through data encryption, its limitations in multicast delivery pose challenges in OSPF communications. In contrast, GRE tunnel supports multicast route delivery required for OSPF, making it a more efficient choice in this context. This study provides insight into the advantages and disadvantages of each protocol for implementing a secure and efficient network.